Pengaruh Leverage Terhadap Kinerja Keuangan Perusahaan Yang Terdaftar Di Bursa Efek Indonesia Pada Indeks Saham LQ 45 - I Gusti Ayu Meirah Putricia; Erwin Febriansyah; Mirra Sri Wahyuni; Meiffa Herfianti (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Financial performance is a crucial indicator used to evaluate a company's effectiveness in managing its financial resources and generating returns for stakeholders. Companies listed in the LQ45 Index on the Indonesia Stock Exchange (IDX) often experience fluctuations in financial performance due to various internal and external factors, one of which is leverage. This study investigates the effect of leverage on the financial performance of companies included in the LQ45 Index. The research addresses the issue of whether the use of debt financing contributes positively to corporate financial performance. A quantitative research approach was employed using secondary data obtained from the first-quarter financial statements of 45 companies listed in the LQ45 Index in 2024. Leverage was measured using the Debt-to-Asset Ratio (DAR), while financial performance was proxied by Return on Assets (ROA). Data analysis was conducted using the Statistical Package for Social Sciences (SPSS), including classical assumption tests and multiple linear regression analysis. The findings reveal that leverage has a positive and statistically significant effect on financial performance, indicating that companies with higher leverage tend to achieve better financial outcomes when debt is managed effectively. The regression results show a significance value of 0.049, supporting the acceptance of the alternative hypothesis. This study contributes to the literature on corporate finance by providing empirical evidence regarding the role of leverage in enhancing financial performance among leading publicly listed companies in Indonesia. The findings also offer practical insights for corporate managers in optimizing capital structure decisions and for investors in evaluating investment opportunities within the LQ45 Index.